PENGARUH ETIKA PROFESI, PROFESIONALISME, INDEPENDENSI, DAN KOMITMEN ORGANISASI TERHADAP KINERJA AUDITOR INTERNAL - Bhaskoro, Ahmad Panji; Ulupui, I Gusti Ketut Agung; Musyaffi, Ayatulloh Michael (LPPM Universitas Bina Bangsa, 2024)
This research was conducted with the aim of determining the influence of professional ethics, professionalism, independence and organizational commitment on the performance of internal auditors. This research uses primary data using a research instrument in the form of a questionnaire. The respondents in this research were the Auditors of the Main Inspectorate of the Central Jakarta National Narcotics Agency (BNN). The sampling technique uses a saturated sampling technique with a total of 60 auditors as respondents. The analysis used is Descriptive Statistical Analysis and Inferential Statistical Analysis using the SmartPLS 4.0 program. The results of this research show that Professionalism and Organizational Commitment have a positive effect on Internal Auditor Performance, while Professional Ethics and Independence have no effect on Internal Auditor Performance